The Effectiveness Of Word Jigsaw Strategy On Students’ Vocabulary Mastery Of Descriptive Text - Wahyuddin; Muhamad Sanusi; Hendrawan (JPSL : Jurnal Pendidikan, Sosial dan Lingkungan, 2023)
The aim of the present study was to find out the empirical evidence whether Word JigsawStrategy on students’ vocabulary achievement of descriptive text was effective to be used inteaching vocabulary at the eighth grade of SMPN 5 Dompu. This present study wasquantitative method with a quasi-experimental design. The sample of this study consisted of 25 students from VIII-3 class for Experimental Group and 25 students from VIII-4 in thecontrolled group. This present study, for the experimental class was taught by using WordJigsaw as strategy in teaching Vocabulary Mastery, while controlled class was taughtwithout Word Jigsaw. The research instrument was test that consisted of pre-test and posttest form. The technique used in collecting data was quantitative with t-test. The result of ttest (post-test) showed that the mean score of experimental group (M = 72,80) was higher than control group (M = 57,60), and independent-samples t-test which values of the sig 2- tailed was 0,2% or 0,002 and 0,002 < 0,05. Thus, it was concluded that Word Jigsaw Strategy was effective on students’ vocabulary mastery of descriptive text.